ANALISIS PEMBELIAN BAHAN BAKU MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA PT OUTDOOR FOOTWEAR NETWORKS - Ramadhanti, Putri Bonita; Suswardji, Edi; Putra, R.Aditya Kristamtomo (Manajerial : Jurnal Manajemen dan Sistem Informasi, 2021)
Production activities are closely related to the raw material inventory to avoid the resistance of the production process. The aim of this research is to know the optimal preperation method for the company y comparing the method of the company and Economic Order Quantiy (EOQ) method. Also determines the amount of frequency ordered, safety stock and reorder point. Research is done with a descriptive and qualitative approach by conducting observations and interiews, as well as collecting documents related to the analysis. The results of this study showed that the company can save 74% of inventory costs by applying the Economic Order Quantity (EOQ).